2021
DOI: 10.1111/jcpt.13495
|View full text |Cite
|
Sign up to set email alerts
|

A risk factor‐based predictive model for linezolid‐induced anaemia: A 7‐year retrospective study

Abstract: What is known and objective: The primary adverse reaction of linezolid is haematological toxicity, leading to thrombocytopenia and anaemia. This study aimed to investigate the risk factors of linezolid-induced anaemia (LI-AN) and establish a predictive model by multivariate logistic regression model analysis to predict LI-AN risks in Chinese adult patients.Methods: Demographic and clinical data of patients who underwent linezolid therapy for more than three days between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“… 34 Twenty studies (80%) reported about prognostic models 31–39 , 41–50 , 54 and 5 studies (20%) about diagnostic models. 30 , 40 , 51–53 While 17 studies (68%) investigated a single ADE, 31 , 33–41 , 43–47 , 49 , 50 8 studies (32%) investigated multiple ADEs. 30 , 32 , 42 , 47 , 51–54 Only 1 study (4%) reported the involvement of key stakeholders before model development.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 34 Twenty studies (80%) reported about prognostic models 31–39 , 41–50 , 54 and 5 studies (20%) about diagnostic models. 30 , 40 , 51–53 While 17 studies (68%) investigated a single ADE, 31 , 33–41 , 43–47 , 49 , 50 8 studies (32%) investigated multiple ADEs. 30 , 32 , 42 , 47 , 51–54 Only 1 study (4%) reported the involvement of key stakeholders before model development.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies used various approaches to retrieve or generate ADE labels and could broadly be categorized into 3 categories: 5 category I studies using ADEs that were registered by healthcare providers (20%), 30 , 33 , 51–53 3 category II studies using adverse event signals followed by a(n) (formal) ADE causality assessment (12%), 43 , 44 , 46 and 15 category III studies using adverse event signals without a(n) (formal) ADE causality assessment (60%). 31 , 34–39 , 41 , 42 , 45 , 46 , 48–50 , 54 Studies in the first category retrieved International Classification of Diseases version 9 or 10 codes (ICD-9 or ICD-10) 55 , 56 that explicitly describe a causal relation between a drug and an adverse symptom (eg, ICD-10 code I95.1: Hypotension due to drugs ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations